Effects of emergency department length of stay on inpatient utilization and mortality - Kai-Jie Ma; Yi-Chen Hsu; Wei-Wen Pan; Ming-Hsien Chou; Wei‑Sheng Chung; Jong-Yi Wang (Health Economics Review)
Abstract Introduction The annual increase in emergency department (ED) visits in Taiwan has led to overcrowding in major hospitals and extended patient stays in the ED. International studies suggest that prolonged ED stays may influence healthcare costs and clinical outcomes for hospitalized patients. However, such investigations are scarce in Taiwan. This study aims to explore the effects of ED stay duration on inpatient medical utilization and mortality risk. Methods This study analyzed data from 42,139 patients at a central Taiwan medical center, using generalized estimating equations (GEE) to evaluate hospital stay duration and costs. Logistic regression assessed mortality risks after hospitalization. Results GEE analysis showed longer ED stays led to increased hospital stays: patients with 24–48 h in the ED had an additional 2.27 days (P < 0.001), and those with ≥ 48 h had an additional 3.22 days (P < 0.001). Logistic regression indicated higher mortality risks for patients with 24–48 h (OR = 1.73, P < 0.001) and ≥ 48 h (OR = 2.23, P < 0.001) in the ED compared to those with ≤ 2 h. Conversely, longer ED stays were associated with lower hospitalization costs; patients with ≥ 48 h in the ED incurred $1,211 less in costs compared to those with ≤ 2 h (P < 0.001). Logistic regression revealed that longer ED stays were linked to higher mortality risks, with patients staying 24–48 h in the ED showing an OR of 1.726 (P < 0.001) and those with ≥ 48 h an OR of 2.225 (P < 0.001). Conclusion Prolonged ED stays are associated with longer hospital stays, higher mortality risks, and lower hospitalization costs due to resource consumption in the ED. These findings highlight the need for strategies to reduce ED stay durations to improve patient outcomes and optimize resource use.